Corporate Tax and Stakeholders’ Benefits in a Challenging Economy: Evidence from Nigeria - Timah, Benson Pyagbara (New Innovations in Economics, Business and Management Vol. 9, 2022)
The study was undertaken to investigate the relationship between corporate tax and benefits of stakeholders (employees, investors, and the host communities). Primarily, the study investigated the relationship between corporate tax and employees’ wages, dividend, and corporate social responsibility (expenditure). Descriptive research design was adopted and data on selected manufacturing companies were collected from the published annual financial statements of the companies. Ordinary Least Squares was employed in the analysis of data with the aid of E-views software. It was found that there was a significant relationship between corporate tax and wage incidences, and between corporate tax and dividend payment. In addition, it was found that there existed a significant, positive relationship between corporate tax and corporate social expenditure of the selected companies. By implication therefore, the findings revealed that tax payment is a source of motivation for greater hard work, which portends better wage incidences payable to employees, more dividend payment, and more to expend on corporate social responsibility.